Implementation of School Exercise Training Program as Prevention of Musculoskeletal Disorders (MSDS) in Students - Romadhoni, Dea Linia; Ramadhani, Alinda Nur (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Musculoskeletal Disorders (MSDs) are a form of disorders that occurs in muscles, bones, joints, ligaments and tendons. Globally, Musculoskeletal Disorders are one of the most common health problems that occur in all ages and genders. Musculoskeletal pain is one of the most common problems in Musculoskeletal Disorders, which can cause various limitations in activity and participation. Musculoskeletal pain can occur in all ages and genders, including children and adolescents. Several studies show that musculoskeletal pain most commonly occurs in the vertebrae, trunk, neck, upper extremities and lower extremities. Musculoskeletal pain in MSDs can cause various negative impacts such as reduced learning motivation, academic failure and learning problems in student. The purpose of this study is to determine the effect of implementing a school exercise training program as a prevention of Musculoskeletal Disorders. Subjects and Method: This was a quasi experiment with no control group. Total sample of 60 children was selected for this study. The dependent variables were spinal curve deformity, degree of forward head posture, and MSDs pain. The independent variable was school exercise program. Mean score before and after intervention were tested using Wilcoxon t test. Results: After implementing the school exercise program, spinal curve deformity (p=0.025), the degree of forward head posture (p=0.046), and MSDs pain (p=0.001) were all observed to decrease. Conclusion: Implementing exercise programs in schools can help prevent musculoskeletal disorders among school children.